A Protecting‐Group‐Free Synthesis of (−)‐Salvinorin A. Issue 29 (2nd May 2021) - Zimdars, Patrick; Wang, Yuzhou; Metz, Peter
Abstract: A concise enantioselective total synthesis of the neoclerodane diterpene (−)‐salvinorin A is reported. The stereogenic center at C‐12 was installed by catalytic asymmetric propargylation with excellent enantioselectivity, and the remaining six stereogenic centers were set up highly diastereoselectively under substrate control. As for our previous synthesis of racemic salvinorin A, two intramolecular Diels‐Alder reactions were applied to generate the tricyclic core. A chemoselective Mitsunobu inversion of a syn 1, 2‐diol allowed for further streamlining of the original reaction sequence by two steps. Overall, (−)‐salvinorin A was synthesized in only 16 steps starting from 3‐furaldehyde with 1.4 % total yield. Furthermore, an alternative intramolecular Diels‐Alder strategy employing a 2‐bromo‐1, 3‐diene moiety was investigated. Abstract : A divine sage : The potent KOR agonist (−)‐salvinorin A was synthesized in only sixteen steps by modification of our previous route to the racemic title compound. Transition to asymmetric synthesis succeeded by a highly enantioselective propargylation to install the stereogenic center at C‐12. Shortening of the original reaction sequence by two steps was finally achieved using a chemoselective Mitsunobu esterification of a cyclic syn 1, 2‐diol. Furthermore, an alternative intramolecular Diels‐Alder strategy employing a 2‐bromo‐1, 3‐diene moiety was investigated.